PENGENALAN BUDAYA POPULER JEPANG DI SMU NEGERI 4 SEMARANG - Hastuti, Nur; Mulyadi, Budi (Departemen Linguistik, Fakultas Ilmu Budaya Universitas Diponegoro, 2023)
ABSTRACTThis research is about Japanese popular culture. The purpose of this research is to examine what types of Japanese popular culture are and how the history and other features of popular culture are described. This research uses lecture media. The method used is descriptive analysis. The data source in this research is Japanese popular culture. The data is then analyzed and interpreted, after which the data is presented in the form of a description and then concluded.Keywords: popular culture, anime, cosplay